تأثير برنامج تحفيظ القرآن الكريم على إتقان المفردات العربية لدى طلاب الصف التاسع في مدرسة د.و.د المتوسطة الإسلامية المتكاملة ميدان - Salwa Haifa; Khoirul Jamil (Universitas Muhammadiyah Gorontalo, 2025)
This study aims to examine the effect of the Tahfidz Al-Qur’an program on the mastery of Arabic vocabulary among ninth-grade students at SMP Islam Terpadu DOD Medan. The research employed a quantitative approach using a quasi-experimental method. The research design utilized pre-test and post-test measurements. The research instruments were proven to be valid and reliable, and the data demonstrated a normal distribution, allowing for the appropriate application of parametric statistical analysis. The results indicate that the Tahfidz program significantly improves students’ vocabulary mastery, with an average N-Gain score of 91.07 (high category) and a t-test result significant at 0.00 (